Relationship Between Serum Amyloid A3 In Serum And Milk Of Mastitic Cows (Applied Biological Research, 2015)
Bovine mastitis, an important disease of dairy cattle, causes a significant change  in normal milk composition as well as changes the overall blood biochemistry. We  grouped the animals of Jersey and Holstein Frisian (HF) crossbred into normal,  subclinical and clinical mastitis groups (n = 10 each) based on clinical history and  diagnostic tests. The serum albumin showed a non-significant variation between  the groups of both breeds following mastitis at subclinical and clinical stages.  Mammary assosiated serum amyloid A3 (M-SAA3) protein in serum of Jersey  crossbred cows showed non-significant difference between the groups, while in  milk significant rise in M-SAA3 levels between mastitic groups was observed. In  HF crossbred, there was significant increase in M-SAA3 levels in both milk and  serum. The study revealed that M-SAA3 is a positive acute phase protein (APP)  in both milk and serum and could be used as an adjunct biomarker to diagnose  subclinical mastitis.
Keywords: Acute phase protein; biomarker; albumin; bovine; mastitis; M-SAA3